(untitled) - Kennedy, David M.; David M. Kennedy (New York, 2001)
The Depression was both a disaster and an opportunity. As David Kennedy vividly demonstrates, the economic crisis of the 1930s was far more than a simple reaction to the alleged excesses of the 1920s. For more than a century before 1929, America's unbridled industrial revolution had gyrated through repeated boom and bust cycles, wastefully consuming capital and inflicting untold misery on city and countryside alike
Keywords: Depressions; New Deal; 1933-1939; World War; 1939-1945